2000
DOI: 10.1046/j.1460-9568.2000.00098.x
|View full text |Cite
|
Sign up to set email alerts
|

IAP family proteins delay motoneuron cell death in vivo

Abstract: Neuronal apoptosis inhibitory protein (NAIP), and human inhibitors of apoptosis 1 and 2 (HIAP1 and HIAP2) are three members of the mammalian family of antiapoptosis proteins called 'inhibitors of apoptosis' (IAP). These molecules can prevent apoptosis in vitro and the over-expression of NAIP can decrease ischemic damage in the hippocampus. The goal of our experiments was to determine whether administration of NAIP, HIAP1 and HAIP2 could rescue motoneurons following axotomy of a peripheral nerve. In young rats,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(50 citation statements)
references
References 32 publications
(90 reference statements)
3
46
0
1
Order By: Relevance
“…A number of laboratories have shown that NAIP is antiapoptotic and cytoprotective in a variety of cellular and in vivo models (Liston et al, 1996;Xu et al, 1997;Perrelet et al, 2000), suggesting that NAIP is an important regulator of neuronal apoptosis. However, a mechanism of NAIP action has not yet been described.…”
Section: Discussionmentioning
confidence: 99%
“…A number of laboratories have shown that NAIP is antiapoptotic and cytoprotective in a variety of cellular and in vivo models (Liston et al, 1996;Xu et al, 1997;Perrelet et al, 2000), suggesting that NAIP is an important regulator of neuronal apoptosis. However, a mechanism of NAIP action has not yet been described.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps most significantly, functional rescue of memory and learning ability was demonstrated (Xu et al, 1997. Adenoviral vectors encoding NAIP, c-IAP1, and c-IAP2 have been shown to suppress apoptosis in the sciatic nerve axotomy model (Perrelet et al, 2000(Perrelet et al, , 2002, and adeno-XIAP in an optic nerve axotomy model (Kugler et al, 2000). Additionally, NAIP overexpression has been shown to be protective both histologically and functionally in the 6-hydroxydopamine model of Parkinson's disease (Crocker et al, 2001).…”
Section: Iap-based Therapeuticsmentioning
confidence: 99%
“…Motor neurons are the target for gene therapy of motor neuron diseases (Baumgartner & Shine, 1998;Perrelet et al, 2000;Mazarakis et al, 2001;Sakamoto et al, 2003;Azzouz et al, 2004b). Therefore, we studied retrograde gene transfer of the HiRet vector into motor neurons in the hindbrain and spinal cord.…”
Section: Hindbrain/spinal Motor Neuronsmentioning
confidence: 99%
“…These viral vectors, when injected into the striatum, deliver the genes through retrograde transport into nigrostriatal dopamine neurons that are the major target for gene therapy of Parkinson's disease (Zheng et al, 2005;Barkats et al, 2006). Intramuscular injection of the vectors also delivers retrogradely the genes into motor neurons that are the target for gene therapy of motor neuron diseases (Baumgartner & Shine, 1998;Perrelet et al, 2000;Mazarakis et al, 2001;Sakamoto et al, 2003;Azzouz et al, 2004b). To enhance the gene transfer of a human immunodeficiency virus type-1 (HIV-1)-based vector via retrograde transport, we have previously generated the HIV-1 vector pseudotyped with a selective variant of rabies virus glycoprotein (RV-G) (Kato et al, 2007).…”
Section: Introductionmentioning
confidence: 99%